Influence of seasonality and gonad development on the nutritional quality and safety of the razor clam Sinonovacula constricta (Lamarck 1818) - HU, Yuan; ZHOU, Chaosheng; ZHU, Jie; KE, Aiyin; XU, Huibin; ZHENG, Yinuo; XU, Jilin (Food Science and Technology, 2023)
Understanding the reproductive activity or seasonal variation in comprehensive evaluations of the nutritional quality and safety of the razor clam Sinonovacula constricta (Lamarck) is important for improving product quality and economic benefits. The contents of moisture (from 80.12±0.38 to 84.98±0.40%), protein (from 53.14±0.06 to 63.12±0.69% DW), lipid (from 4.55±0.19 to 5.69±0.35% DW), glycogen (from 5.40±1.11 to 16.13±1.55% DW), and ash (from 12.03±0.33 to 19.86±0.56% DW) varied significantly at different gonadal development cycles or seasons. Glycogen, lipid, and protein variations were closely associated with gonadal development, with the lowest levels of lipid and protein in the spawning period. Moreover, S. constricta consistently had a well-balanced essential amino acid profile throughout the year, indicating that it is a source of high-quality protein. The predominant free amino acids in S. constricta were taurine, glycine, lysine, and alanine, which are important contributors to the flavor. S. constricta was defined as lean fat throughout the gonad cycle with polyunsaturated fatty acid accounting for the majority in the active and maturing stages. Microbiological quality and total volatile basic nitrogen were associated with the alteration of seasons. The optimal harvesting time of S. constricta was the inactive stage of most gonads in spring (from March to April in Taizhou, Zhejiang Province, China).